1990
DOI: 10.1002/ijc.2910460613
|View full text |Cite
|
Sign up to set email alerts
|

Lymphokine‐activated killer cell cytotoxicity against human colon carcinomas enhanced by monoclonal antibody D612

Abstract: The antibody-dependent cellular cytotoxicity (ADCC) properties of a murine monoclonal antibody (MAb), designated D612 (IgG2a), which reacts with human colon carcinomas, was studied using normal human peripheral blood lymphocytes (PBMNC). Although the level of ADCC of PBMNC with D612 varied among different donors, it was 20 to 30 times higher than the lytic activity of control cultures containing isotype-matched control MAb. Incubation of PBMNC with recombinant interleukin-2 (IL-2) resulted in a 2- to 5-fold au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…How to maintain the persistent activity of transferred immunocytes in vivo is still a key challenge. Ettinghausen et al (1987) firstly reported the immunotherapy effects of recombinant IL-2 in cancer patients and IL-2 could lead to an increase of NK cells and LAK cells (Pendurthi et al, 1990). Besides, the immune-enhancing effects of IL-2, IL-15, IL-12, and IL-18 on antitumor cytotoxic function and immunophenotype of NK cells are also been investigated in melanoma patients (Martinovi c et al, 2015;Vuletic et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…How to maintain the persistent activity of transferred immunocytes in vivo is still a key challenge. Ettinghausen et al (1987) firstly reported the immunotherapy effects of recombinant IL-2 in cancer patients and IL-2 could lead to an increase of NK cells and LAK cells (Pendurthi et al, 1990). Besides, the immune-enhancing effects of IL-2, IL-15, IL-12, and IL-18 on antitumor cytotoxic function and immunophenotype of NK cells are also been investigated in melanoma patients (Martinovi c et al, 2015;Vuletic et al, 2015).…”
Section: Introductionmentioning
confidence: 99%